Gambaran Tingkat Pengetahuan Siswa terhadap Demam Berdarah Dengue di SDN 18 Delta Pawan - Fath Dwisari; Abdurraafi’ Maududi Dermawan; Nurza Wahyuningsih; Samsiah Samsiah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The public health quandary in Indonesia encompasses the presence of Dengue Hemorrhagic Fever (DHF). DHF is frequently encountered in tropical and subtropical regions. The World Health Organization (WHO) has recorded Indonesia as the nation with the highest incidence of DHF in Southeast Asia. To avert DHF, it is imperative to engage in routine eradication of mosquito breeding grounds. Moreover, augmenting public cognizance and comprehension regarding DHF prevention through educational outreach is of paramount importance. The objective of this initiative is to ascertain the level of knowledge about DHF among students at SDN 18 Delta Pawan, Delta Pawan District, Ketapang Regency. The methodology employed includes lectures, discussions, and Q&A sessions, with a sample size of 35 respondents. The findings revealed that the students' knowledge at SDN 18 Delta Pawan fell into the High category for 12 students (34.3%) and the Low category for 23 students (65.7%). It can be inferred that this educational outreach was fairly beneficial in enhancing the students' knowledge about dengue hemorrhagic fever at SDN 18 Delta Pawan.